STRATEGI KEPALA MADRASAH DALAM PEMBINAAN AKHLAKUL KARIMAH SISWA DI MADRASAH IBTIDAIYAH SWASTA MIFTAHUL FALAH TELAGASARI KARAWANG - Saeroji; Eliva Sukma Cipta; Fitriyani Kosasih (STKIP Subang, 2026)
The development of students' moral character has become one of the primary goals of Islamic education, requiring effective leadership from the head of the madrasah to establish a conducive educational environment. This study aims to analyze the strategies implemented by the head of Madrasah Ibtidaiyah Swasta Miftahul Falah Telagasari Karawang in fostering students' akhlakul karimah. A qualitative approach employing a case study design was used to obtain an in-depth understanding of leadership practices in character development. Data were collected through observation, interviews, and documentation, and analyzed using the interactive model of data condensation, data display, and conclusion drawing. The findings indicate that the head of the madrasah implemented several strategic approaches, including strengthening religious school culture, establishing habitual religious activities, promoting exemplary behavior among teachers and staff, enforcing educational discipline, organizing character-oriented extracurricular activities, and strengthening collaboration with parents. These strategies created a supportive learning environment that encouraged students to develop honesty, discipline, responsibility, politeness, social awareness, and religious commitment. Despite challenges arising from diverse family backgrounds, social influences, and the rapid development of digital technology, continuous evaluation and collaboration among school stakeholders contributed to the effectiveness of character development programs. The study concludes that the leadership strategies of the head of the madrasah play a significant role in fostering students' akhlakul karimah through systematic, consistent, and sustainable character-building practices integrated into all aspects of school life.